Desprendimiento de placenta normoinserta en embarazo prematuro de 33 semanas - Mendieta Acosta, Eloisa Elizabeth (2018)
The premature detachment of placenta normoinserta is the second most frequent cause of hemorrhages in the second and third trimesters of pregnancy, Although the main cause of premature detachment of placenta normoinserta is unknown, it is associated with etiological factors such as pathological hypertension, genetic factors, traumatisms , multiple pregnancies, tobacco, and cocaine. The classic triad of symptoms in the premature detachment of normoinserta placenta are: hemorrhages, pain and uterine hypertonia. The most frequent complications are related to massive hemorrhage and the alteration of coagulation. Its etiology is multifactorial and can come to understand the life of both the mother and the fetus. The prognosis depends on the degree of detachment, the precocity of the diagnosis and a correct treatment we must consider it as an emergency because probably the next hours are crucial as much as the patient and the fetus, its severity depends on the time that elapses between the start of the symptoms and the attention received. The treatment should include general measures for maintaining the hemodynamic balance. We must know the problem about maternal and perinatal health and achieve a greater and better clinical understanding and with an early diagnosis, management and adequate treatment to avoid maternal and fetal morbidity and mortality